Ant schnapps for health and pleasure: the use of Formica rufa L. (Hymenoptera: Formicidae) to flavour aquavit - Ingvar Svanberg; Åsa Berggren (BMC, 2019)
Abstract Background The relationship between humans and insects goes long back and is important. Insects provide a multitude of ecosystem services for humans, e g. by pollinating crops and decomposing matter. Our current knowledge about the cultural ecosystem services that insects provide is limited and not much examined. Method Scattered ethnographical descriptions and folklore records from pre-modern Sweden and other Scandinavian countries give us insights into local knowledge and use of insects among the peasantry in various parts of the country. These data have been analysed and critically reviewed. Source pluralism has been used as a method. Results The mound-building red wood ant, Formica rufa L., is one of the species that were used in Sweden for their healing properties. It was a widespread belief that the formic acid could be used to cure various diseases, especially gout and rheumatism. Both anthills and the ants themselves were used for that purpose. It was also common to flavour distilled liquor (brännvin) with ants; a remedy used for medicinal purposes. However, already in the eighteenth century, this was also used as schnapps. The cultural services provided by this species stretches throughout history and still exists today. Conclusion While the use of ants in medicine has vanished, the custom of making homemade ant flavoured alcoholic beverage survives in Sweden. Nowadays it is a hobby among people who flavour their own aquavit. It is appreciated as a tasty and interesting drink.